Performance of oyster mushroom (Pleurotus ostreatus) grown on different fingermillet husk substrates - Sanjel, Priyanka; Shrestha, Ram Kumar; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Substrate type is one of the major factors affecting the growth and yield of oyster mushroom (Pleurotus ostreatus). Five substrates; Finger millet husk, Fingermillet husk + Molasses, Fingermillet husk + Rice bran, Fingermillet husk + Wheat bran, Fingermillet husk +Mustard oilseed cake, were evaluated for growth and productivity of oyster mushroom. The experiment was conducted in a completely randomized design with each treatment replicated seven times. Additives were added on finger millet husk @5% of its dry weight. Standard cultivation practice was followed with steam sterilization and spawning was done in poly bags containing 2.5 kg of wet substrate. Data were collected on time taken for full spawn run, fresh mushroom yield, biological efficiency and cropping duration upto three flushes. Molasses took the least duration (16.86 days) for full spawn run which was found to be statistically at par with wheat bran(17.13 days) and rice bran(17.75 days) whereas control treatment took the longest duration (21.62 days). Rice bran produced the highest fresh mushroom yield (793.04g/bag) with highest biological efficiency (137.92%), which was statistically at par with control, molasses and wheat bran. Similarly, rice bran had least cropping duration (66.62 days) followed by control (67.88 days), molasses (69.14 days), wheat bran (70.12 days) and mustard oilseed cake (73.86 days). The lowest fresh yield (521.84 g/bag) with lowest biological efficiency (90.75%) and the longest cropping duration (73.86 days) was observed on mustard oilseed cake supplementation. This study revealed that molasses, rice bran and wheat bran accelerated spawn run whereas mustard oilseed cake supplementation produced lowest fresh mushroom yield with least biological efficiency and highest cropping duration showing that it was ineffective for increasing yield and productivity of oyster mushroom.